THE LEGAL STATUS OF RELIGIOUS MINORITIES IN ISLAM: A HISTORICAL PERSPECTIVE - SHAKEEL AHMAD WANI; SAYED AAQIB QADRI; BILAL AHMAD WANI (Hamdard Islamicus, 2023)
This paper deals with the concept of Dhimmi (non-Muslims living in an Islamic state) and the laws formulated for them in Islam, which lie at the centre of the intellectual discourses on the Islamic legal and political system vis-à-vis the issues of tolerance, democracy, and human rights. The teachings of Islam, as revealed to the Prophet Muhammad (×aÌrat Muhammad RasËlullah KhÉtam un NabiyyÊn Øallallahu ‘alaihi wa ‘alÉ  Ólihi wa AÎÍÉbihi wa Øallam) provide complete guidance for attaining success and glory in this world and the hereafter. As a comprehensive way of life, Islam encompasses a unique socio-economic and political system. It deals with all private and public life aspects and local and international affairs. However, the status and treatment of minorities in Muslim societies (especially in the context of Islamic law) have been of special concern to Muslim and non-Muslim scholars alike. It has also been a much-debated subject among Orientalists, who have created many misinterpretations regarding it. In light of these problems, this paper has attempted to establish a discourse on a three-fold level: it has argued that laws about minorities in Islam are based on the concept of justice, how these laws are significant in the emancipation of humanity in general, and the minorities (non-Muslims living in an Islamic state) in particular has been highlighted; and the relevant Quranic verses, Prophetic traditions, and, the Muslim statesmen’s practices and juristic views regulating the principles of how Muslims are supposed to interact with non-Muslims have been examined as well. To achieve these objectives, descriptive, analytical, and exploratory methods have been followed throughout the paper.